Pengaruh Pembelajaran Pendidikan Agama Kristen pada Remaja di Era Industri 4.0 - Eka Putri Jayanti (Jurnal Salvation, 2021)
Abstract: Christian Religious Education Learning, is an important part of educating adolescents in the industrial era 4.0. Advances in technology have both a positive and negative impact on Christian youth. This negative impact can make teenagers lose their way and even cannot distinguish the truth as written in God's Word. Learning Christian religious education must open itself to be able to enter the world of adolescents to understand and organize strategies so that Christian religious education learning is accepted, understood and becomes a part of youth. This journal aims to find the concept of the influence of Christian Religious Education learning on adolescents in the industrial era 4.0. with the aim to better understand the influence of Christian Religious Education learning on adolescents as an important part of written commands in the script   Abstrak: Pembelajaran Pendidikan Agama Kristen, adalah bagian penting dalam mendidik remaja di era indutri 4.0. Kemajuan teknologi berdampak positif dan berdampak negatif untuk remaja Kristen. Dampak negatif tersebut bisa membuat remaja kehilangan arah bahkan tidak dapat membedakan kebenaran seperti tertulis dalam Firman Tuhan. Pembelajaran pendidikan Agama Kristen harus membuka diri untuk bisa masuk dalam dunia remaja untuk memahami dan mengatur strategi agar pembelajaran Pendidikan Agama Kristen di terima, dipahami dan menjadi bagian diri dari remaja. Jurnal ini bertujuan untuk menemukan konsep pengaruh pembelajaran Pendidikan Agama Kristen pada remaja di era industri 4.0. dengan tujuan untuk lebih memahami pengaruh pembelajaran Pendidikan Agama Kristen pada remaja sebagai bagian penting perintah yang tertulis dialkitab